Using Thermal Inertia of Buildings with Phase Change Material for Demand Response. (September 2017) - Rahimpour, Zahra; Faccani, Alice; Azuatalam, Donald; Chapman, Archie; Verbič, Gregor
Abstract: In recent years, demand response programs have proved useful in managing peak demand and meeting sustainability goals, enabling an efficient use of the smart grid. Heating, ventilation, and air conditioning (HVAC) loads in buildings constitute a large proportion of the total energy consumption of households, and accordingly, a flexible and efficient operation of these devices can aid power utilities in meeting load management objectives while reducing consumer's electricity bills. With the emergence of promising new technologies, such as phase change materials (PCM), buildings can serve as a virtual thermal energy storage, which improves energy efficiency and also allows occupants to offer grid services like peak demand reduction. The objective of this paper is to establish the effectiveness of PCM as a demand response resource, demonstrating the extent to which it can be used for peak demand reduction. A wide range of scenarios are considered to investigate the impacts of geographical location, PCM melting point, duration of precooling and preheating, setting points of HVAC system, thickness and location of PCM, on the capability of the PCM in reducing or shifting the cooling and heating load. All simulations are performed using the EnergyPlus platform, examining typical residential buildings in five Australian cities: Brisbane, Sydney, Melbourne, Hobart and Perth. The simulation results showed a decrease in the HVAC demand in the buildings with PCM, in all cities, with the highest reductions observed in Hobart and Melbourne. The integration of a 20mm thick PCM in the roof, wall and floor of the building yielded a 21.8% and 16.7% reduction in annual HVAC demand in Hobart and Melbourne respectively, when compared to the building without PCM. However, this is with the assumption that the HVAC system is operating 24 hours a day for a whole year. The PCM-integrated building showed a shift in the HVAC demand in all cities except Perth. A shift by 9 minutes, 3 minutes, 60 minutes and 103 minutes was recorded in the cities of Brisbane, Sydney, Melbourne and Hobart respectively. The simulation results will be used in subsequent research to schedule the HVAC demand using a home energy management system.